Profiling Temporal Changes of the Pineal Transcriptomes at Single Cell Level Upon Neonatal HIBD - Ding, Xin; Pan, Tao; Tian, Qiuyan; Huang, Wenxi; Hayashi, Lauren S; Liu, Qin; Li, Fuyong; Xu, Li-Xiao; Miao, Po; Yang, Xiaofeng; Sun, Bin; Feng, Chen-Xi; et al. (Frontiers in Cell and Developmental Biology, 2022)
Neonatal hypoxic-ischemic brain damage (HIBD) often results in various neurological deficits. Among them, a common, yet often neglected, symptom is circadian rhythm disorders. Previous studies revealed that the occurrence of cysts in the pineal gland, an organ known to regulate circadian rhythm, is associated with circadian problems in children with HIBD. However, the underlying mechanisms of pineal dependent dysfunctions post HIBD remain largely elusive. Here, by performing 10x single cell RNA sequencing, we firstly molecularly identified distinct pineal cell types and explored their transcriptome changes at single cell level at 24h and 72h post neonatal HIBD. Bioinformatic analysis of cell prioritization showed that both subtypes of pinealocytes, the predominant component of the pineal gland, were mostly affected. We then went further to investigate how distinct pineal cell types responded to neonatal HIBD. Within pinealocytes, we revealed a molecularly defined  to  subtype conversion induced by neonatal HIBD. Within astrocytes, we discovered that all three subtypes responded to neonatal HIBD, with differential expression of reactive astrocytes markers. Two subtypes of microglia cells were both activated by HIBD, marked by up-regulation of Ccl3. Notably, microglia cells showed substantial reduction at 72h post HIBD. Further investigation revealed that pyroptosis preferentially occurred in pineal microglia through NLRP3-Caspase-1-GSDMD signaling pathway. Taken together, our results delineated temporal changes of molecular and cellular events occurring in the pineal gland following neonatal HIBD. By revealing pyroptosis in the pineal gland, our study also provided potential therapeutic targets for preventing extravasation of pineal pathology and thus improving circadian rhythm dysfunction in neonates with HIBD.